Pathogenicity of two species of entomopathogenic agents to subterranean termite Coptotermes gestroi Wasmann (Isoptera: Rhinotermitidae) in laboratory. Pathogenic effcts of two species of entomopathogenic agents, Metarhizium anisopliae and Bacillus thuringiensis A ard B, were trested to subterranean termite Coptotermes gestroi Wasmann in laboratory. Three groups of rhc tcrti~ite tclor.ker:s were each e.xposed to a treated filter paper with one of the entomopathogenic agents for one minute. Twenty - Paimin Sukartana; Rusti Rushelia; Widi Rumini (Buletin Hama dan Penyakit Tumbuhan, 2000)
Pathogenicity of two species of entomopathogenic agents to subterranean termite Coptotermes gestroi Wasmann (Isoptera: Rhinotermitidae) in laboratory. Pathogenic effcts of two species of entomopathogenic agents, Metarhizium anisopliae and Bacillus thuringiensis A ard B, were trested to subterranean termite Coptotermes gestroi Wasmann in laboratory. Three groups of rhc tcrti~ite tclor.ker:s were each e.xposed to a treated filter paper with one of the entomopathogenic agents for one minute. Twenty-five termite workers and three soldiers were then transferred to a wetfilter paper disk that had been installed in a plastic vial. The test materials were stored in a dark and humid at room temperature for 14 dc~j'.s. Five replicates were provided. Observations were conducted daily to determine termite nlortality urld take out dead termites. Reszllts showed that the fungus M. anisopliae was more pathogenic than Bt. A and B. After being exposed to treated paper with the fungus, all test termites died within 8-10 days. Treatments with B. thuringierisis A and B did not produce high mortality, and seemed to be not different from the control, only causing less than 3% termite mortality until the end of the tests.